Canadian beef and dairy farmers' attitudes towards animal vaccines. (8th August 2019) - Ugochukwu, Albert I.; Phillips, Peter W. B.
Abstract : The willingness to pay (WTP) approach is increasingly being used in different disciplines to assess peoples' readiness to accept change. This paper assesses the potential for two subunit vaccines for the prevention and control of bovine tuberculosis and paratuberculosis in cattle. A survey of beef and dairy farmers was conducted across Canada to identify factors that influence their WTP for subunit vaccines. Estimated results of the interval‐data model indicate that the size of a farmer's cattle herd, neighbourhood effect, and buyer recommendations for vaccination significantly influence farmers' WTP while veterinarians appear to be the most critical pathway for farmers to source information on new vaccine options. The mean willingness to pay amounts for both vaccines reveals that farmers are likely to use the vaccines if the costs are kept at reasonable level.